Changes in the content of biodegradable organic matter in tap water in the city of Częstochowa = Zmiany zawartości biodegradowalnej materii organicznej w wodzie wodociągowej dla miasta Częstochowy - Rakocz, Klaudia; Rosińska, Agata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper presents research aimed at the assessment of biodegradable organic carbon content changes (BDOC) during water disinfection process. The water samples examined in the research came from intakes, pumping stations at treatment plants situated in the Silesia district and water consumers. The examined water was underground water.
Keywords: biodegradowalny węgiel organiczny; wody podziemne; dezynfekcja; jakość wody; biodegradable organic carbon; underground water; disinfection; water quality